Roulette Sebagai Media Inovatif dalam Meningkatkan Partisipasi Siswa pada Aktivitas Kebugaran Jasmani Siswa Sekolah Dasar: Penelitian - Bimo Putro Asdo; Lokananta Teguh Hari Wiguno; Anang Marzuqi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This article aims to increase student participation in physical fitness activities through the use of innovative roulette media. The method I used was Classroom Action Research (CAR) with a quantitative approach involving 28 elementary school students. The main instrument used was a student participation observation sheet with five indicators: attendance, involvement, enthusiasm, cooperation, and obedience. The results showed a significant increase in student participation from before the action (average participation value of 67.27) to the first cycle (75.54) and increased again in the second cycle (82.44). The use of roulette media seems very effective in creating a fun, interactive learning atmosphere, and is able to encourage active student involvement in physical activities. These findings reinforce the importance of learning media innovation in increasing student motivation and participation in elementary schools.